PERTANGGUNGJAWABAN PIDANA GATEKEEPER DALAM TINDAK PIDANA PENCUCIAN UANG - Diana Darmayanti Putong, 031217017315 (2016)
Crimes increase rapidly following the globalization of the world. The development of a crime generates money laundering, with various levels or figures. One of the figures is to use the services of professionals such as lawyers, public notary, accountants, which referred to as Gatekeepers. The role of gatekeeper in money laundering can be seen as follows by establishing a shell company (ex: panama papers case), by decrease tax in the selling property agreement (notaries EM in Djoko Susilo case). With the high numbers of gatekeeper in the case involving of money laundering. Group of eight (G-8) concern also rises by bringing up the gatekeeper initiative(ex: client due diligence, report suspicious transaction) in Moscow Communique.Which was later included in the FATF Forty Recommendation. Gatekeeper initiative offers a solution resulted from the international community to prevent the gatekeeper involvement in money laundering but there are still have any problem in term of preventive money laundering conducted by the gatekeepers. The main issue is to seek the criminal responsibility of the gatekeeper who has committed in money laundering. In order to articulate the criminal responsibility of gatekeepers, formulating principle of equality before the law and fairness justice. The implementation of the equality before the law and fairness justice because the principles is taken into account in order to gain their mistake since they are being as intellectual actors, complicity and key persons in the field of investigation assets. Technically, a person or a profession with some special qualifications referring to their competence may be categorized as Propira Act.This dissertation using the normative legal method with statute approach, conceptual approach, comparative approach. Gatekeeper in Propira Act have a purpose to conduct money laundering. To sum up, this dissertation offers the three concepts of a criminal responsibility, as follows the actis against the law, intention or negligence, and breach of ethics. Based on the need of criminal responsibility of this matter, there should be a criminal policy as a form of crime prevention (due diligence, reporting, monitoring) and the eradication (sanctions, asset search investigation, forfeiture). Keyword: Criminal Responsibility, Gatekeeper, Money Laundering